Biorefinery - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Muhammad Najib, Muhammad Nor (Penerbit UMP, 2011)
A biorefinery is a facility that integrates biomass conversion process...